Genetic or therapeutic disruption of the Reelin/Apoer2 signaling pathway improves inflammatory arthritis outcomes - Laurent Calvier; Catherine R. Wasser; E. Blair Solow; Sharon Wu; Bret M. Evers; David S. Karp; Maria Z. Kounnas; Joachim Herz (Proceedings of the National Academy of Sciences, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by synovial inflammation, pannus formation, and progressive joint destruction. The inflammatory milieu in RA drives endothelial cell activation and upregulation of adhesion molecules, thus facilitating leukocyte infiltration into the synovium. Reelin, a circulating glycoprotein previously implicated in endothelial activation and leukocyte recruitment in diseases such as atherosclerosis and multiple sclerosis, has emerged as a potential upstream regulator of these processes. However, its role in RA pathogenesis remains poorly understood. Here, we demonstrate that Reelin levels are markedly elevated in the plasma of both RA patients and mouse models of arthritis, with higher concentrations correlating with greater disease severity. Genetic deletion of the Reelin receptor Apoer2 conferred significant protection against serum transfer arthritis (STA), underscoring the relevance of this pathway in disease progression. Furthermore, therapeutic inhibition of Reelin using the CR-50 antibody yielded robust anti-inflammatory effects in multiple preclinical arthritis models, including STA, K/BxN, and collagen-induced arthritis. Notably, CR-50 treatment not only reduced leukocyte infiltration and synovial inflammation but also mitigated pannus formation. Importantly, these benefits were achieved without the gastrointestinal side effects commonly associated with nonsteroidal anti-inflammatory drugs like diclofenac. Our findings position Reelin as a proinflammatory endothelial biomarker and therapeutic target in RA. By modulating endothelial activation and leukocyte recruitment, anti-Reelin strategies offer an alternative approach to attenuate synovial inflammation and joint damage. These results provide a compelling rationale for further exploration of Reelin-targeted therapies as alternatives to conventional immunosuppressive treatments in RA and other chronic inflammatory diseases.